The influence of nutrients on the increased risk of developing endometriosis - Zwierzyńska, Anna; Gruszka, Jakub; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2023)
Diet and nutrition are fundamental to women’s health. This condition is affected by both deficiencies and excesses of nutrients. Nutrition affects gene expression, susceptibility to disease through various mechanisms. It affects the expression of genes by changing them, and also affects various diseases, including endometriosis. This disease is quite common and often has a negative impact on women’s quality of life.